1977
DOI: 10.1084/jem.146.3.673
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic recognition of influenza virus-infected cells. II. Expression of influenza A matrix protein on the infected cell surface and its role in recognition by cross-reactive cytotoxic T cells

Abstract: Two distinct subpopulations of cytotoxic T cells are generated in the primary or secondary response of mice to type A influenza viruses. One subpopulation is specific for the immunizing virus strain. The other subpopulation shows a high degree of cross-reactivity for heterologous type A virus of a different subtype. This report examines the possibility that distinct influenza virus antigens, expressed on the surface of the infected cell, are recognized by the different subpopulations of influenza-specific cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0
1

Year Published

1978
1978
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 27 publications
1
69
0
1
Order By: Relevance
“…The present findings are therefore consistent with the concept that influenza hemagglutinin glycoprotein is a target antigen for the strainspecific CTL subpopulation stimulated by infectious influenza virus. Also consistent with this concept is our previous observation that nascent viral glycoprotein synthesis is required to render target cells susceptible to lysis by strain-specific CTLs (11). It is also evident from the present results showing that the high degree of cross-reactivity for target cells infected with type A influenza virus of unrelated subtypes, which is generated in response to infectious influenza virus (16,23,24) and is likewise mediated by a discrete subpopulation of cross-reactive CTLs (10,16,23) cannot be readily explained on the basis of reactivity to the influenza hemagglutinin.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The present findings are therefore consistent with the concept that influenza hemagglutinin glycoprotein is a target antigen for the strainspecific CTL subpopulation stimulated by infectious influenza virus. Also consistent with this concept is our previous observation that nascent viral glycoprotein synthesis is required to render target cells susceptible to lysis by strain-specific CTLs (11). It is also evident from the present results showing that the high degree of cross-reactivity for target cells infected with type A influenza virus of unrelated subtypes, which is generated in response to infectious influenza virus (16,23,24) and is likewise mediated by a discrete subpopulation of cross-reactive CTLs (10,16,23) cannot be readily explained on the basis of reactivity to the influenza hemagglutinin.…”
Section: Discussionsupporting
confidence: 79%
“…It is also evident from the present results showing that the high degree of cross-reactivity for target cells infected with type A influenza virus of unrelated subtypes, which is generated in response to infectious influenza virus (16,23,24) and is likewise mediated by a discrete subpopulation of cross-reactive CTLs (10,16,23) cannot be readily explained on the basis of reactivity to the influenza hemagglutinin. Although CTLs directed to the influenza N have not as yet been directly demonstrated, it is reasonable to assume that such CTLs would have specificity characteristics comparable to those reported here for CTLs directed to influenza H. Thus, at present, the most likely candidate for the target antigen of the cross-reactive cytotoxic subpopulation is the internal virion antigen influenza matrix protein which is serologically cross-reactive among all type A influenza viruses and expressed on the surface of influenza-infected cells (11,28,29).…”
Section: Discussionmentioning
confidence: 52%
“…For example, CTLs induced by recombinant clone 65 (which bears the type I S1 genome segment) gave 30% specific 51Cr release on type III-infected syngeneic targets at the highest effector/target ratio (33:1). This same degree of lysis was seen at the lowest effector/target ratio (4:1) on targets infected with 65 1 1 1 3 3 3 3 1 3 1 802 3 1 3 1 3 3 3 3 3 3 III 3 3 3 3 3 3 3 3 3 3 94 3 3 1 1 3 3 1 1 (7)(8)(9)(10). At least two populations of CTLs are generated from host lymphocytes stimulated by type A influenza.…”
Section: Resultsmentioning
confidence: 59%
“…The question of which viral antigens are recognized by CTLs has recently been addressed by use of influenza and vesicular stomatitis viruses (7)(8)(9)(10)(11)(12). The use of subtypes of influenza A virus has shown that the hemagglutinin is one of the proteins recognized by cytotoxic T cells (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…As shown in Table 1 Spleen lymphocytes of memory mice primed 3-12 weeks previously with IQ'' HAU (haemagglutiriiiting units) A/WSN virus by intraperitoneal injection were re-stimulated 1/ 1 vitro in bulk culture as described elsewhere (Braciale. 1977).…”
Section: H-2 Specificity Of Antiviral Tc Tested On Tumour Target Cellsmentioning
confidence: 99%